Towards the construction of socio-technical systems to contribute to the reduction of digital divides in the territories of Araucanía, Chile (Sociología y tecnociencia, 2026)
There is still an unresolved debate about the relationship between technology and inequality. This article addresses digital inequality as a political problem rather than a technical one. Aiming to understand digital inequalities in the territories of La Araucanía, Chile, it was considered pertinent to contribute theoretical value from the perspective of sociotechnical controversies and the Social Construction of Technology. A theoretical model comprising four axes is proposed: technological infrastructure, connectivity policies and regulations, territorial approach and geographic digital divide, and the subjective experience of people on the network. The methodology used was controversy mapping based on the definition of two case studies. The main results highlight that the proposed model allowed “opening the black box” of digital inequality, establishing the different positions of the actors, associations, and disputes. They allow observing its main facets and deepening a societal problem, referring to the market model that governs connectivity in Chile.
Keywords: Sociotechnical systems; digital divides; digital experience.